A comparative analysis of urban development and the tram line network in Lviv in 1932−2016 - Cegiełko Szczepan; Karsznia Izabela (Polish Cartographical Review, 2020)
This article presents a comprehensive analysis of changes in urban development (including certain types of public buildings) and changes in the routes of Lviv’s tram lines over the last 80 years, related to the territorial and demographic development of the city. For this purpose, maps comparing these elements of urban infrastructure between 1932 and 2016 were developed. The analysis was carried out based on a plan of Lviv from 1932, contemporary vector data taken from OpenStreetMap, ArcGIS basemaps, Google Street View panoramic images, information contained in interwar Lviv guides, and supplementary information from other sources.